Getting COVID-19: Anticipated negative emotions are worse than experienced negative emotions. (March 2023) - Dillard, Amanda J.; Meier, Brian P.
Abstract: Objective: When people think about negative events that may occur in the future, they tend to overestimate their emotional reactions, and these "affective forecasts" can influence their present behavior (Wilson and Gilbert, 2003). The present research examined affective forecasting for COVID-19 infection including the associations between emotions and preventive intentions and behavior. Methods: In two studies, we compared individuals' anticipated emotions and recalled emotions for COVID-19 infection. Study 1 asked college students ( N  = 219) and Study 2 asked general adults ( N  = 401) to either predict their emotions in response to a future COVID-19 infection or to recall their emotions associated with a previous infection. Results: In both studies, reliable differences in negative emotions emerged. Those who were predicting their feelings associated with a future infection anticipated more negative emotion than those who were recalling their feelings associated with a past infection reported. Greater negative emotion in both studies was significantly associated with being more likely to have been vaccinated as well as higher intentions to get the booster vaccine. Conclusions: These findings suggest that compared to those who have had a COVID-19 infection, those who have not yet experienced infection anticipate they will experience greater negative emotion, and this may have implications for preventive behaviors. In general, these findings suggest that people may have an impact bias for COVID-19 infection. Highlights: Anticipated and recalled negative emotions for COVID-19 infection were compared. People who have never had COVID may overestimate their negative emotion for infection. More negative emotion, particularly when anticipated, relates to vaccination and intentions.